Benefits of Self Confidence to Ability Student Mathematical Problem Solving - Meidina Purnama Putri; Juariah Juariah; Tika Karlina Rachmawati (UIN Sunan Gunung Djati Bandung, 2022)
Mathematics is a subject that has an important position in the learning system at the elementary school to high school level, this is because in real life every day, consciously or unconsciously, it definitely requires the role of mathematics. Based on the above, the author intends to suggest another side that is useful in studying mathematics, especially those related to students' mathematical problem solving abilities in terms of the benefits of self-confidence. The purpose of this study was to analyze the benefits of students' self confidence on mathematical problem solving abilities. The benefits of this self-confidence need to be revealed and known by the various parties involved so that learning mathematics is more enjoyable and can arouse students' motivation to study harder with optimal results. The method used in this research is literature study. With this method the authors search, read, record, and analyze research articles related to titles published in accredited journals, with the help of Google Scholar by including the keywords